Short vs Standard Duration Dual Antiplatelet Therapy after Percutaneous Coronary Intervention with New-Generation Drug-Eluting Stents: A Meta- Analysis - Ullah, Inam; Muhammad, Muhammad Afaq; Muhammad Haidar Zaman; Khan, Umair Khan (Journal of University College of Medicine and Dentistry, 2024)
Objective: In patients with coronary artery disease, dual antiplatelet therapy (DAPT) is recommended after percutaneous coronary intervention, but the duration is still debated. This meta-analysis compared short-duration (1 to 3 months) to standard-time (twelve months) double antiplatelet treatment in patients who received coronary intervention with new generation drug eluting Stent. Methodology: To conduct this examination, we methodically looked at PubMed, Cochrane CENTRAL, Embase, and Web of Science databases for randomized controlled trials, evaluating varying durations of double antiplatelet treatment following new generation stents implantation from July to September 2023. Seven randomized controlled trials were included with a total of 22,945 patients. The primary efficacy endpoint was the incidence of Major adverse cardiovascular events, such as cardiac mortality, heart attack, stent coagulation, and target vessel revascularization; while the safety endpoint was the incidence major bleeding. Secondary endpoints were major adverse cardiovascular and cerebro-vascular complications, any bleeding, and net adverse cardiovascular incidence for a year after stent implantation. Results: Short-time DAPT was linked to a significantly less incidence of major bleeding (0.8% vs 1.5%), any bleeding (2.5% vs 4.2%) and NACE (2.5% vs 4.2%) compared to standard duration of DAPT. No significant variation was noticed among the two groups regarding major adverse cardiovascular events (4.1% vs. 4.2%) and acute cardiovascular and cerebrovascular incidents (4.7% vs. 4.8%). Short-duration DAPT in patients with acute coronary syndrome was linked with decreased risk of bleeding and net adverse cardiovascular events. Conclusion: Short-duration DAPT significantly lowers bleeding risk and reduces net clinical adverse events without increasing ischemic risk, making it a reasonable choice for people with new-generation drug eluting stents, particularly those with high bleeding risk or recent surgery.